2013
DOI: 10.1177/0267659112472385
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic perfusion during cardiopulmonary bypass and postoperative temperature are independent predictors of acute kidney injury following cardiac surgery

Abstract: Acute kidney injury (AKI) following cardiopulmonary bypass (CPB) is associated with increased mortality, requirement for dialysis, and longer intensive care unit (ICU) and hospital length of stay. Rewarming during CPB and poor oxygen delivery have been associated with AKI; however, the role of temperature management on AKI has not been clearly defined. This study aims to evaluate the role of hyperthermia during CPB and the temperature upon admission to the ICU on AKI following cardiac surgery, using the RIFLE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 19 publications
4
35
2
Order By: Relevance
“…This finding was supported by Newland and colleagues [29] (2013), who reported an arterial outlet temperature higher than 37 C is an independent predictor of acute kidney injury.…”
Section: Peak Warming Temperature Gradient and Rewarming Ratesupporting
confidence: 55%
See 1 more Smart Citation
“…This finding was supported by Newland and colleagues [29] (2013), who reported an arterial outlet temperature higher than 37 C is an independent predictor of acute kidney injury.…”
Section: Peak Warming Temperature Gradient and Rewarming Ratesupporting
confidence: 55%
“…Groom and coworkers [28] (2004) reported an association with hyperthermia (defined as a peak core temperature >37.9 C) and an increased rate of mediastinitis. Newland and colleagues [29] reported in 2013 that an arterial outlet temperature exceeding 37 C during CPB is an independent predictor of acute kidney injury.…”
Section: Avoidance Of Hyperthermiamentioning
confidence: 99%
“…However, while some researchers have noted that higher MAP and systemic oxygen delivery were renoprotective in early AKI and precluded disease progression [33], others have reported that high MAP did not reduce the risk of post-operative AKI during normothermic CPB, or change the duration of hospitalization and mortality rate [34]. In one study, critically ill patients with early AKI and DO2I > 450 mL/min/m 2 within the first 12 h of diagnosing the early stage of the disease had a significantly lower susceptibility of progressing to late disease in comparison to patients with DO2I < 450 mL/min/m Interestingly, the findings of another study showed that hyperthermic CPB was an independent predictor of AKI, as avoiding arterial outlet hyperthermia may help to reduce AKI risk [35]. Furthermore, few evidence-based studies indicated that the avoidance of hypotension in stage I AKI, by for instance maintaining MAP at less than 70-75 mmHg, may reduce the incidence of stage III AKI [36,37].…”
Section: Hemodynamic and Acid-base Parameters As Predictors And Prognmentioning
confidence: 99%
“…Rewarming after CPB and hyperthermic perfusion during CPB are novel risk factors for AKI after cardiac surgery [66, 67]. A recent systematic review of perioperative interventions aimed to optimize global blood flow showed no difference in mortality, but the rates of renal failure (relative risk (RR) 0.71, 95% confidence interval (CI) 0.57 to 0.90) were reduced [68].…”
Section: Risk Factors For Akimentioning
confidence: 99%